Montmorillonite/Tripolyphosphate Crosslinked Chitosan Nanocomposites for Eco-Friendly Agricultural Applications - Siriphannon, Punnama; Rungkron, Suthida; Soetsom, Sunisa; Sukyee, Suriya (My University, 2023)
Natural montmorillonite (MMT) was facilely impregnated with a mixed solution of protonated chitosan (CS) and KNO3, which was then subsequently impregnated with sodium tripolyphosphate (TPP) to ionically crosslink with chitosan, resulting in the MMT/xCS-20KNO3-TPP nanocomposites. The initial content of chitosan to MMT was varied from 2.5, 5 and 10 wt%, and while the TPP:chitosan weight ratio was kept at 1:5. The K+ and NO3- ions interacted ionically and were entrapped in the MMT basal spacing and the free volume of TPP crosslinked chitosan of the MMT/xCS-20KNO3-TPP nanocomposites. These nanocomposites were able to successfully prolong the K+ and NO3- releases, in which the cumulative released values (%R) ranging from 21 – 26 % for K+ and 0.37 – 0.65 % for NO3-. The presence of protonated amine in the chitosan played the dominant effect on the release profile of NO3- ion more than that of the K+ ion. The higher the chitosan content employed in the impregnation method, the more crosslinked chitosan structure in the MMT/xCS-20KNO3-TPP nanocomposites, resulting in decreased K+ and NO3-releases at each pre-determined soaking duration. The MMT/xCS-20KNO3-TPP nanocomposites have been considered as a promising choice for environmentally friendly fertilizers.
Keywords: chitosan; impregnation; montmorillonite; nanocomposites; slow-release fertilizer